Mapping the Landscape of E-Government Research in Village Governance: Trends, Challenges, and Opportunities - Syarifuddin, Haeruddin; Rahmat Razak, Muhammad Rais; Lubis, Sandi; Mir., Sajad Ahmad (Department of Government Studies, Universitas Muhammadiyah Buton., 2024)
This study aims to map the development and research trends of e-government in village governance. The research method applied is a systematic literature review using 538 scientific articles from the Scopus database published between 2019 and 2024. The review was conducted using bibliometric analysis processed through R-Studio (Biblioshiny) and Tableau applications. The study results revealed a steady increase in publication trends, the formation of multiple author collaboration networks, and the identification of key thematic clusters such as digitalization, public service delivery, governance frameworks, trust, and technology adoption. The thematic evolution analysis also demonstrated the emergence of new research areas, including blockchain, cybersecurity, and participatory governance. The limitation of this study is that the articles used are only sourced from the Scopus database, which may not fully represent the broader landscape of global research on village-level e-government. Future research needs to incorporate scientific articles from other reputable international databases, such as Web of Science and Dimensions Scholars, to provide a more comprehensive understanding of the evolving discourse in this field.